Harnessing the power of cruciferous vegetables: developing a biomarker for Brassica vegetable consumption using urinary 3,3′-diindolylmethane - Fujioka, Naomi (Cancer Prev Res (Phila), 2016)
Glucobrassicin in Brassica vegetables gives rise to indole-3-carbinol, a compound with potent anti-cancer effects in preclinical models. We previously showed that the urinary metabolite 3,3′-diindolylmethane (DIM) could discriminate between volunteers fed high and low doses of Brassica vegetables. However, the quantitative relationship between glucobrassicin exposure and urinary DIM level is unclear. We conducted a clinical trial to examine the hypotheses that a range of glucobrassicin exposure from Brassica vegetables is reflected in urinary DIM, and that this effect plateaus. Forty-five subjects consumed vegetables, a mixture of Brussels sprouts and/or cabbage, at 1 of 7 discrete dose levels of glucobrassicin ranging from 25 to 500 μmol, once daily for two consecutive days. All urine was collected for 24 hours after each vegetable-eating session. Urinary DIM was measured using our published liquid chromatography-electrospray ionization-tandem mass spectrometry-selected reaction monitoring (LC/ESI-MS/MS-SRM) method. Urinary DIM excretion increased predictably with increasing glucobrassicin dose and plateaued between 200 and 300 μmol of glucobrassicin. The association between glucobrassicin dose and urinary DIM was strong and positive (R(2)=0.68). The majority of DIM was excreted in the first 12 hours after vegetable consumption. We conclude that urinary DIM is a reliable biomarker of glucobrassicin exposure and I3C uptake, and that feeding glucobrassicin beyond 200 μmol did not consistently lead to more urinary DIM, suggesting a plateau in potential chemopreventive benefit.